Assistance to prisoners of war from regional branches of the Russian society of the Red Cross in august 1914 — october 1917 (with the city of Krasnoyarsk of Yenisey guberniya as an example) - Olesya Dolidovich (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The article is devoted to such an area of activity of the regional branches of the Russian Society of the Red Cross during the First World War as providing assistance to Russian prisoners of war. Materials from the city of Krasnoyarsk, Yenisei province, show that this work was primarily carried out by women’s committees. The scale of assistance did not correspond to the real needs of prisoners, and was reduced throughout the war due to unfavorable changes in the economy. The capabilities of the regional branches of the society were further reduced after February 1917 due to a shortage of material resources. Historical experience shows that public initiative is not enough to protect fellow prisoners of war. An active role of the state is needed, implementing measures in various fields, including diplomatic and economic, in order to improve the material and living conditions, food supplies, and medical care for prisoners of war. Without such government intervention, prisoners in enemy countries are an extremely vulnerable group of people, subject to violence and arbitrariness.